EXTRACTION OF PYRETHRINS FROM Chrysanthemumcinerariaefolium PETALS AND STUDY ITS ACTIVITY AGAINSTBEETLE FLOUR Tribolium castanum - Shawkat, Muayad; Khazaal, Ali; Majeed, Majid (Iraqi Journal of Science, 2024)
The production of Pyrethrins as an insecticide from Chrysanthemumcinerariaefolium flowers was studied. The crude active compound was extractedusing organic solvents. Detection by HPLC proved that the extract containedPyrethrin I and Pyrethrin II compared to the standard compounds. The flowersextract showed active biological effect against beetle flour Tribolium castanumreached 100% at the concentration 40% while the mortality percent reached 60, 77%when the concentration decreased to 20 or 30% respectively.